(untitled) (International Conference on Computers in Education, 2023)
Artificial intelligence in education (AIED) is the use of artificial intelligence techniques and tools to enhance and support learning and teaching processes. However, AIED also raises ethical challenges related to transparency, which is the ability to understand how AIED systems make decisions that influence educational outcomes. This paper reviews the literature on transparency in AIED, and presents a set of learner centric guidelines for ensuring transparency. The paper uses the Transparency Index Framework by Chaudhry et al. (2022) as a guiding tool, and discusses the best practices for providing information, allowing oversight, and respecting rights and choices in AIED. The paper also illustrates these practices with examples of ethically and transparently designed AIED systems. The paper concludes by highlighting the trade-offs and precautions involved in ensuring transparency in AIED, and suggests future research directions. This paper contributes to the ethical discourse on transparency in AIED by providing a comprehensive overview, identifying the best practices and challenges, and proposing the learner centric guidelines.